Morphological and genetic diversity analysis in selected Vernonia lines - Ramalema, Seganka Piet (My University, 2007)
Vernonia (Vernonia galamensis) is a new potential industrial oilseed crop. The seeds of this crop contain unusual naturally epoxidised fatty acids which are used in the production of various industrial products. The objective of this study was to evaluate the genetic diversity of selected vernonia lines in Limpopo Province through morphological, seed oil content and RAPD DNA markers. Significant differences were observed for days to 50 % flowering (93 - 140 days), plant height (141.80 - 166.33 cm), number of productive primary heads (29 - 60 head/plant), number of productive secondary heads (12 - 30 head/plant), thousand seed weight (1.85 - 3.52 g) and seed yield (454.44 - 786.85 kg/ha) between lines. Further results from oil analysis showed differences in the contents of seed oil (22.4 - 29.05%), vernolic acid (73.09 - 76.83%), linoleic acid (13.02 - 14.05%), oleic acid (3.77 - 5.28%), palmitic acid (2.48 - 2.98%) and stearic acid (2.26 - 2.75%). Among 13 RAPD DNA primers screened, primer OPA10 amplified DNA samples and resulted in four distinct groupings among tested lines. Four promising lines were selected viz. Vge-16, Vge-20, Vge-27 and Vge-32 displaying greater seed yield, increased vernolic acid content and reduced number of days to 50 % flowering.
Thesis (M.Sc. (Agriculture)) --University of Limpopo, 2007
Keywords: Vernonia; Genetics (Biology) -- South Africa; Vernonia plants